Analisis Perilaku, Kepribadian Introvert Mahasiswa terhadap Partisipasi dalam pembelajaran Bahasa Indonesia - Rizki, Muhammad (Universitas Negeri Padang, 2024)
This study examines the impact of introverted personality traits on student participation in Indonesian language learning at the higher education level. Introverted students often prefer self-reflection and observation over active participation in class discussions, potentially affecting their comprehension, particularly in a subject that also serves to convey national and cultural identity. Data were collected through interviews and observations of Sekolah Tinggi Ilmu Ekonomi Balikpapan students. The findings reveal that introverted characteristics, such as selective engagement and a tendency for isolation, influence their interactions and classroom involvement. To foster inclusive participation, project-based and inclusive teaching methods are recommended, emphasizing the need to accommodate diverse learning styles.